Subclinical inflammation markers and their impact on obstetric outcomes in abortus imminens: A case-control study - Başkıran, Yusuf; Uçkan, Kazım; Çeleğen, İzzet (Annals of Medical Research, 2023)
Aim: The aim of the study is to investigate the relationship of subclinical inflammatory factors Platelet crit (PCT), Neutrophil-lymphocyte ratio (NLR), Monocyte-lymphocyte ratio (MLR), Platelet-lymphocyte ratio (PLR) obtained from complete blood count (CBC) with Abortion Immunes (AI) and obstetric results.In recent years, studies reveal that subclinical inflammatory markers can be used as an indicator of the inflammatory process in many diseases. Few studies have evaluated indicators of inflammation and postpartum outcomes in abortion imminent patients.Material and Methods: The study was conducted between January 2020 and January 2021. A total of 429 pregnant women, 203 of whom were pregnant with AI and 226 who were healthy, were included in the study.Results: PCT, NLR, and MLR values were significantly higher and PLR values were low in the AI group (p 0.22, NLR > 2.29, and MLR > 0.20 were significantly associated with an increased risk of AI (P
Keywords: Abortus imminens; Inflammation; Platelet crit; Neutrophil to lymphocyte ratio; Platelet to lymphocyte ratio; Monocytes to lymphocyte ratio